2010
DOI: 10.1177/1352458510391339
|View full text |Cite
|
Sign up to set email alerts
|

Effects of long-term resistance training and simultaneous electro-stimulation on muscle strength and functional mobility in multiple sclerosis

Abstract: Background. Resistance training studies in MS often use short intervention periods.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

8
97
1
2

Year Published

2014
2014
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 107 publications
(108 citation statements)
references
References 59 publications
8
97
1
2
Order By: Relevance
“…1 Due to the variety of functional disability in patients with MS, rehabilitation intervention, especially exercise therapy, is a necessary part of their treatment protocol. 2 In general, different types of exercise therapy are used to enhance functional activity, muscle strength, and mobility in patients with MS. [3][4][5] The results of these studies showed not only that aerobic exercises can cause physiologic changes 5 and improve ambulatory function and fatigue 6 but also that strength training exercise can increase muscle fiber size 7 and muscle strength 3 and improve functional activities and balance in patients with MS. 4 In a systematic review study, the authors suggested that "resistance training of moderate intensity seems to be well tolerated and to have beneficial effects on patients with MS." 8(p51) Endurance and resistance training sessions have been designed based on concentric contraction (contraction accompanied by shortening of muscle length, eg, uphill walking) of the involved muscles, which causes muscular hypertrophy and improves functional activity. 9 It must be pointed out that these types of exercises are generally considered high-intensity training (60%-80% of the maximum voluntary contraction force), which may tire out patients with MS. 10 However, some research has shown that eccentric exercise training (contraction accompanied by elongation of muscle length, eg, downhill walking), compared with concentric exercise, may improve balance in elderly people 11 and increase muscle strength in patients with Parkinson disease 12 and MS. 13 This is due to its potential for high muscle force production at a uniquely low energy cost 14 so that downhill walking (as a model of eccentric exercise) requires less energy cost than uphill walking (as a model of concentric exercise).…”
mentioning
confidence: 99%
“…1 Due to the variety of functional disability in patients with MS, rehabilitation intervention, especially exercise therapy, is a necessary part of their treatment protocol. 2 In general, different types of exercise therapy are used to enhance functional activity, muscle strength, and mobility in patients with MS. [3][4][5] The results of these studies showed not only that aerobic exercises can cause physiologic changes 5 and improve ambulatory function and fatigue 6 but also that strength training exercise can increase muscle fiber size 7 and muscle strength 3 and improve functional activities and balance in patients with MS. 4 In a systematic review study, the authors suggested that "resistance training of moderate intensity seems to be well tolerated and to have beneficial effects on patients with MS." 8(p51) Endurance and resistance training sessions have been designed based on concentric contraction (contraction accompanied by shortening of muscle length, eg, uphill walking) of the involved muscles, which causes muscular hypertrophy and improves functional activity. 9 It must be pointed out that these types of exercises are generally considered high-intensity training (60%-80% of the maximum voluntary contraction force), which may tire out patients with MS. 10 However, some research has shown that eccentric exercise training (contraction accompanied by elongation of muscle length, eg, downhill walking), compared with concentric exercise, may improve balance in elderly people 11 and increase muscle strength in patients with Parkinson disease 12 and MS. 13 This is due to its potential for high muscle force production at a uniquely low energy cost 14 so that downhill walking (as a model of eccentric exercise) requires less energy cost than uphill walking (as a model of concentric exercise).…”
mentioning
confidence: 99%
“…Only three studies in the systematic review of PRT 1 measured balance; two studies found an increase in functional reach, 5,6 and one did not find an effect on balance measured by a force platform. 7 The effect of PRT on balance therefore remains unclear, and the specificity of training principle may once again come into play.…”
Section: Proposalmentioning
confidence: 99%
“…A randomised controlled trial involving 36 patients highlighted that long-term intense resistance training improved muscle strength (maximal isometric strength of both knee extensor and flexor muscles), but did not change dynamic muscle strength and functional mobility [31].…”
Section: Jmir Serious Games [33]mentioning
confidence: 99%